Miskonsepsi Pembelajaran IPAS Siswa Kelas IV Sekolah Dasar - Rahmawati, Putri; Kurniawati, Wahyu (Universitas Muhammadiyah Magelang, 2024)
The purpose of the study was to clarify or explain the misconceptions in IPAS learning for force material for grade IV elementary school students. Data collection methods using tests in the form of diagnostic tests and interviews. The sampling method is a saturated sample of all fourth grade elementary school students. The research data were analyzed using quantitative descriptive analysis. Based on the research results, an average of 39.75% of misconceptions experienced by elementary school students or 15 out of 39 students are included in the